(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The article analyzes the practice of developing coherent speech in preschool children by teaching them to compose stories in the conditions of Uzbekistan. The results of the study show that creating stories based on pictures and fairy tales, dramatic games and interactive exercises significantly increase children’s vocabulary, grammatical structure and logical consistency. The article provides methodological recommendations for educators.